Studies in Austral Bryaceae (Bryopsida) I. New Combinations in Ptychostomum Hornsch. from southern South America - Spence, John R. (Phytotaxa, 2020)
The genus Ptychostomum (Bryaceae, Bryopsida) is examined from southern South America including southern Patagonia and Tierra del Fuego regions of Argentina and Chile south of 50o S latitude. Five new combinations transferred from Bryum are made; Ptychostomum dicarpum (E.B. Bartram) J.R. Spence, Ptychostomum chorizodontum (Card. & Broth.) J.R. Spence, Ptychostomum lamprochaete (Dusén) J.R. Spence, Ptychostomum pauperculum (E.B. Bartram) J.R. Spence, and Ptychostomum vernicosum (Dusén) J.R. Spence. Bryum coelophyllum is placed into synonymy under P. nivale. Bryum macrosporum is placed into synonymy under P. chorizodontum. The type of B. pallidoviride represented undetermined material that could not be assigned to any species. A preliminary key to the 20 species of Ptychostomum currently recognized for the region is presented.